Comparison of different insulin pump makes under routine care conditions in adults with Type 1 diabetes. Issue 10 (23rd July 2017) - Leelarathna, L.; Roberts, S. A.; Hindle, A.; Markakis, K.; Alam, T.; Chapman, A.; Morris, J.; Urwin, A.; Jinadev, P.; Rutter, M. K.
Abstract: Aims: To compare long‐term HbA1c changes associated with different insulin pumps during routine care in a large cohort of adults with Type 1 diabetes representative of other clinic populations. Methods: Observational, retrospective study of 508 individuals starting pump therapy between 1999 and 2014 (mean age, 40 years; 55% women; diabetes duration, 20 years; 94% Type 1 diabetes; median follow‐up, 3.7 years). Mixed linear models compared covariate‐adjusted HbA1c changes associated with different pump makes. Results: The pumps compared were: 50% Medtronic, 24% Omnipod, 14% Roche and 12% Animas. Overall HbA1c levels improved and improvements were maintained during a follow‐up extending to 10 years (HbA1c : pre‐continuous subcutaneous insulin infusion (pre‐CSII) vs. 12 months post CSII, 71 (61, 82) vs. 66 (56, 74) mmol/mol; 8.7 (7.7, 9.6) vs. 8.2 (7.3, 8.9)%; P < 0.0001). The percentage of individuals with HbA1c ≥ 64 mmol/mol (8.0%) reduced from a pre‐CSII level of 68% to 55%. After adjusting for baseline confounders, there were no between‐pump differences in HbA1c lowering ( P = 0.44), including a comparison of patch pumps with traditional catheter pumps ( P = 0.63). There were no significant ( P < 0.05) between‐pump differences in HbA1c lowering in pre‐specified subgroups stratified by pre‐pump HbA1c, age or diabetes duration. HbA1c lowering was positively related to baseline HbA1c ( P < 0.001) and diabetes duration ( P = 0.017), and negatively related to the number of years of CSII use ( P = 0.024). Conclusions: Under routine care conditions, there were no covariate‐adjusted differences in HbA1c lowering when comparing different pump makes, including a comparison of patch pumps vs. traditional catheter pumps. Therefore, the choice of CSII make should not be influenced by the desired degree of HbA1c lowering. What's new?: Continuous subcutaneous insulin infusion (CSII) is often considered the 'gold standard' insulin replacement therapy for individuals with Type 1 diabetes. This is the first study to compare long‐term changes in HbA1c associated with different makes of pump under routine care conditions. We found no significant differences in HbA1c improvement when comparing different makes of insulin pump, including a comparison of patch pumps and traditional catheter pumps, and pre‐specified patient subgroups stratified by pre‐CSII HbA1c, age and diabetes duration. The choice of CSII make should not be influenced by the desired degree of HbA1c lowering.